TRUST MODERATION ROLE TOWARDS REVISIT INTEREST IN BANGSRING UNDERWATER TOUR - Kristian Suhartadi Widi Nugraha (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
Tourist can voluntarily do sacrifice in order to get experience when during travel. The important in knowing the tour visitor behaviour can easily push the forming of tourist interest to revisit by minimizing marketing cost. This research aims to test the trust moderation role towards tourist revisit interest in Bangsring Underwater Tour Banyuwangi. Analysis technique used in this research is Moderated Regression Analysis (MRA) with data collection technique through questioner distribution and in-depth interview.This research done by taking respondent of 120 by purposive sampling method. This research result shows that there is no trust variable moderation effect that strengthen the connection between visitor experience with revisit interest. With multiple regression analysis testing proven that trust is predictor factor and together tourist experience and trust have significance impact toward tourist revisit interest Bangsring Underwater Tour increasing.